Reviewing the capacity for transparency and trust offered by the blockchain technology - Linares-Barbero, Manuela (2018)
Trust is a fundamental element of the contemporary world, especially in the different transactions carried out by companies. The increase of fraud, as well as the falsification of products and/or services, has generated that companies must spend money and efforts in implementing reprocesses and security measures. Transparent transactions have become a challenge that many seek to achieve. One of the great proposals of reliable transactions is the blockchain technology. It can offer us transparency in transactions and trust among organizations, even if they do not know each other beforehand. In our article, we will review the literature on the capacity for transparency and trust that the blockchain technology presents in the supply chain.